Situation Report: Romania, 25 April 1978 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Visits United States New Ways of Handling Citizens' Complaints New Law on Civil Defense Co-operative Members' Guaranteed Income Raised New Roman Catholic Official Appointed in Iasi A New Doctor Aslan Case? Signs of Revival in the Romanian Theater?